Policy Reform, Shadow Prices, and Market Prices. (IMF Working Papers; Working Paper ;, 1988)
How should possible policy reforms and projects be assessed when prices give misleading signals? Revenues and costs at market prices then give distorted measures of social gains and losses and our appraisal should use social opportunity costs, or correctly defined, shadow prices. We show how shadow prices may be integrated into an analysis of tax and price reform, demonstrate the critical dependence of these prices on government policy, and analyze their relations with market prices. A conceptual framework for applied analysis is provided plus a detailed theoretical account of policy in a model with some fixed prices, rationing, and taxation.